Controlled Release Products for Managing Insect Pests. (1st August 2016) - Faleiro, J.R.; Al-Shawaf, A.M.; Al-Dandan, A.M.; Al-Odhayb, A.; Al-Rudayni, A.; Abdallah, A.B.; Peixoto, M.P.; Vargas, R.; Bottom, M.; Chidi, S.; Borges, R.; Mafra-Neto, A.
From 1900???2000, the global human population grew by more than 400%, from 1.5 to 6.1 billion. The demands that the current population places upon global food supplies presents what may be one of the greatest challenges of the modern age. To support such a large population in a reliable, sustainable manner, productivity of agricultural crops will have to be improved significantly, most likely through multiple means (development of new, higher-yield crops; more efficient water use; improved cropping systems). One active area of research is the development of more effective methods of agricultural pest management. For much of contemporary history, insect pest management has relied predominantly on conventional insecticides. These insecticides are typically designed as cover sprays with residues covering the entire crop, with the aim of reducing or eliminating the pest population in the treated field. Since the days of Silent Spring, there has been widespread concern over the potential hazards of traditional insecticides to workers, consumers, and the environment, leading to increasingly stringent regulation of their use. Though steps have been taken to minimize the risks posed by pesticide applications, public perception of the suitability of these chemicals remains negative. Over time, more robust regulation may result in the loss of pest control measures upon which many agricultural producers currently depend. In addition to their questionable long-term availability, traditional insecticides possess a number of other limitations, which make the development of alternative methods of pest control highly desirable. One of the most harmful of these shortcomings is the vulnerability of conventional insecticides to resistance, the gradual loss of susceptibility of a target insect to a given toxin over time. Resistance has been shown to occur more rapidly when a single class of toxicants is applied frequently, without variation, over multiple seasons. Therefore, rotation of multiple classes of insecticide to treat the same field is a crucial safeguard to circumvent resistance development, making the loss of more and more pesticide molecules to deregulation an even greater threat to effective long-term pest control. For these reasons, extensive research has been conducted into an alternative control method, requiring no or minimal use of chemical toxicants: semiochemical-based pest management. Semiochemicals ??? compounds that manipulate insect behavior ??? possess many advantages over conventional insecticides. Semiochemicals are naturally occurring compounds with short environmental lives, and are generally viewed as safer, for both people and the environment, than traditional pesticides (reviewed in OECD, 2002). Most semiochemicals used in pest management have been species-specific pheromones (produced by members of the same species to communicate with each other, but eliciting no response in other species), and as such, present fewer risks of negative impacts on beneficial insects. Rather than attempting to eradicate the pest by treating the entire crop with chemical toxicants, semiochemical pest management seeks to reduce pest populations over time, often by non-lethal means, such as mating disruption, which involves application of synthetic sex pheromones to interfere with male insects??? ability to locate a mate. Another promising strategy of semiochemical control is attract and kill (A&K), which consists of blending a semiochemical attractant with a small quantity of toxicant. A&K techniques reduce the amount of pesticide applied per unit area compared to traditional cover sprays, and enable more selective application methods, maximizing impact on the target pest while minimizing risks of crop or environmental contamination, worker exposure, and harmful effects on non-targets. A&K formulations are also less susceptible to the development of resistance: the attractant can typically be formulated with a variety of different toxicants, depending on which insecticides work best against the target insect in a given environment, and on regulatory requirements. Despite these advantages, semiochemical products have seen limited adoption compared to traditional insecticides. Reasons for this limited success are varied. Conventional pesticides have dominated the market for so long that it is difficult for new alternatives to gain traction (technology "lock in"). Additionally, semiochemicals are often applied as one component of an integrated approach to pest management, and so require more in-depth knowledge of the pest???s behavior and ecology to apply effectively than conventional cover sprays. A key limitation of semiochemical technologies in the eyes of prospective users is the high cost of many semiochemical active ingredients (AIs). The volatile nature of these chemicals demands that a relatively large quantity of the AI be applied over the treated area to sustain season-long control. If semiochemical products are to gain wider acceptance among agricultural producers ??? especially if they are to be introduced in developing nations, where food production is most challenging to sustain ??? the affordability and ease-of-use of these products will have to be improved. One way this optimization may be achieved is the formulation of semiochemical AIs into controlled-release technologies. By extending AI field life (protecting it from environmental degradation, refining AI release rate), we can decrease the amount of semiochemical required to treat the crop effectively, lowering the overall cost of the application. In the past, most controlled-release technologies have been hand-applied devices, such as pouches, polyethylene tubes or ropes, and rubber septa-type dispensers. As these products require an investment of time and manpower that would be difficult to implement in large-scale crops, controlled-release technologies amenable to mechanized application would possess a keen competitive edge over the majority of semiochemical products currently on the market.